Massive Integration of Planktonic Cells within a Developing Biofilm - Nay El-Khoury; Imene Bennaceur; Emilie Verplaetse; Stéphane Aymerich; Didier Lereclus; Mireille Kallassy; Michel Gohar (Microorganisms, 2021)
During biofilm growth, the coexistence of planktonic and sessile cells can lead to dynamic exchanges between the two populations. We have monitored the fate of these populations in glass tube assays, where the Bacillus thuringiensis 407 strain produces a floating pellicle. Time-lapse spectrophotometric measurement methods revealed that the planktonic population grew until the pellicle started to be produced. Thereafter, the planktonic population decreased rapidly down to a value close to zero while the biofilm was in continuous growth, showing no dispersal until 120 h of culture. We found that this decrease was induced by the presence of the pellicle, but did not occur when oxygen availability was limited, suggesting that it was independent of cell death or cell sedimentation and that the entire planktonic population has integrated the biofilm. To follow the distribution of recruited planktonic cells within the pellicle, we tagged planktonic cells with GFP and sessile cells with mCherry. Fluorescence binocular microscopy observations revealed that planktonic cells, injected through a 24-h-aged pellicle, were found only in specific areas of the biofilm, where the density of sessile cells was low, showing that spatial heterogeneity can occur between recruited cells and sessile cells in a monospecies biofilm.